International Brigade. British Battalion. National Memorial Meeting : Programme - Bolsover, Philip ; Copeman, Fred, 1907-1983 ; McDade, Alex, 1905-1937 ; Tomalin, Miles ; Green, Nan; Spain. Ejército Popular de la República. Brigada Internacional, XV. (London : Marston, 1939)
1939 SP01-002-86 80 pages : illustrations ; 18 cm. JD 10.P6 PPC 1724